嵌合抗原受体T细胞治疗儿童急性B淋巴细胞白血病异基因造血干细胞移植后复发一例报告并文献复习 (Zhonghua Xue Ye Xue Za Zhi, 2016)
OBJECTIVE: To evaluate the safety and efficacy of chimeric antigen receptors T cells (CAR-T) in childhood acute B lymphoblastic leukemia (B-ALL). METHODS: A relapsed B-ALL child after allogeneic hematopoietic stem cell transplantation (allo-HSCT) was treated with CAR-T, and the related literatures were reviewed. RESULT: An 11-year-old girl with TEL-AML1 fusion gene positive BALL who suffered a bone marrow relapse 28 months after remission from conventional chemotherapy. During the second remission, the patient received haploidentical allo-HSCT. She relapsed with detectable TEL-AML1 fusion gene even after chemotherapy and donor leukocyte infusions. She received an experimental donor-derived fourth generation CD19 CAR-T therapy. After infusion of 1 × 10(6)/kg CAR-T cells, she experienced only mild or moderate cytokine-release syndrome and the minimal residual disease turned negative. Then three maintenance of CAR-T cell infusions [(0.83–1.65)×10(6)/kg] was administered, and the disease-free survival had lasted for 10 months. However, the TEL-AML1 copies in her blood still increased and she died with leukemia relapse after additional CAR-T cell infusion. CONCLUSION: Treatment of relapsed B-ALL with the fourth generation CAR-T cells directed against CD19 was effective and safe. CAR-T therapy is a novel therapeutic approach that could be useful for patients with relapsed and refractory B-ALL who have failed all other treatment options.